THE INFLUENCE OF CROSS SELECTION ON THE EFFICIENCY OF COMMODITY EGG PRODUCTION - Usenko, S. O.; Vasiliva, O. O.; Karunna, T. I.; Shaferivskyi, B. S.; Zeliznyk, I. M.; Kravchenko, O. I. (Scientific Progress & Innovations, 2022)
The article presents the results of the analysis of the possibilities of further development of poultry farms taking into account the existing potential and problems of the modern poultry business. Monitoring of indexes of the productivity of cross-country race of Lomann is conducted in the conditions of PJC the «Poltava poultry factory». The level of productivity of laying hens and the efficiency of using two lines of cross-country Lohmann LSL Light and Lohmann Brown were determined. It was found that Lomann Brown cross-laying hens maintained high viability and good adaptive qualities throughout the egg-laying period, as indicated by the survival rate of 96 %. Despite good adaptation to an intensive housing and use system, the Lohmann LSL Light crossbird had a 2 % lower survival rate than the Lohmann Brown crossbred hen. Studies have shown that Lomann LSL Light crosses the egg-laying peak quickly (91.4 %) and maintains high productivity until the end of its use. At the end of the productive period, the bird of this cross kept egg production at 69.1 %, which exceeds this figure compared to the bird of the cross Lohmann Brown by 3.6 %. However, the average weight of eggs obtained from the Lohmann LSL Light cross was lower compared to the average weight of eggs obtained from the Lohmann Brown cross. However, the cross-country bird Lohmann Brown dynamically increased live weight, and at the end of the productive period had a fairly high weight. Thus, at the end of egg-laying, the live weight of Lohmann LSL Light hens was at the level of 1629, while the hens - laying hens of Lohmann Brown had a live weight – 1880.9 g. It was found that the cost of feed, and consequently the cost of production in the cross Lohmann LSL Light is much lower than in the cross Lohmann Brown. These indicators indicate that the use of laying hens cross Lomann LSL Light in the conditions of PJSC "Poltava Poultry Farm" is more effective compared to the bird cross Lomann Brown.